Quotes, Order Flow, and Price Discovery - BLUME, MARSHALL E.; GOLDSTEIN, MICHAEL A. (Journal of Finance, 1997)
ABSTRACT The goal of this article is to examine the impact of 1975 Congressional mandate to integrate the trading of NYSE‐listed stocks. The conclusions are: most of the time, the New York Stock Exchange (NYSE) quote matches or determines the best displayed quote, and the NYSE is the most frequent initiator of quote changes. Non‐NYSE markets attract a significant portion of their volume when they are posting inferior bids or offers, indicating they obtain order flow for other reasons, such as “payment for order flow.” Yet, when a non‐NYSE market does post a better bid or offer, it does attract additional order flow.